Different aspects of detecting karst with geophysical methods - Tales from the underworld - Solbakk, Terje (NTNU, 2020)
The work in this thesis integrate conventional seismic interpretation, gravity survey data, field data from analogues and state-of-the-art numerical modeling in order to broaden and increase the understanding of the distribution of porosity and permeability derived from chemical dissolution of rocks (karst). Karst porosity from small scales to the large are addressed onshore Norway ( Paper 1), the intermediate scale in the offshore setting of the Loppa High, Barents Sea (Paper 2) and the large scale encompassed the entity of both land and offshore areas of Norway (Paper 3). All papers present new workflows combining geophysical methods and geology for karst mapping and prediction. Furthermore, challenges related to distinguishing pseudokarst from karst were addressed in the two offshore papers (Paper 2 and 3), as well as the geophysical imaging problems related to isomorphs (Paper 2). The first case study area (Paper 1) includes onshore Norway’s largest cave room, within the Svarthammarhola cave system (SHC), located in a Caledonian nappe setting in Nordland. This is the first time microgravimetric data is used for mapping of known and detection of hitherto unknown karst cave passages in Norway, and a workflow is presented for interpretation of assumed karst. Cave passages and karst features of the Svarthammarhola cave, form negative density contrasts expressed in gravity field anomalies. Here, microgravimetric methods are shown to be applicable in challenging geological settings with heterogeneous lithologies. This setting is a good onshore analogue which is highly applicable for offshore settings. Challenges due to heterogeneous infill of large cavities and variations in carbonate facies are also addressed. The workflow covers not only the detection of large cave rooms, but also deals with minor karst features (epikarst) in carbonate rocks. A 3D density model was built utilizing 3D forward modelling aiming on matching model with surface gravity measurements. The most important result relates to distinct ...